Maternal Health: A Case Study of Rajasthan - Iyengar, Sharad D; Iyengar, Kirti; Gupta, Vikram (Journal of Health, Population and Nutrition, 2009)
This case study has used the results of a review of literature to understand the persistence of poor maternal health in Rajasthan, a large state of north India, and to make some conclusions on reasons for the same. The rate of reduction in Rajasthan's maternal mortality ratio (MMR) has been slow, and it has remained at 445 per 1000 livebirths in 2003. The government system provides the bulk of maternal health services. Although the service infrastructure has improved in stages, the availability of maternal health services in rural areas remains poor because of low availability of human resources, especially midwives and clinical specialists, and their non-residence in rural areas. Various national programmes, such as the Family Planning, Child Survival and Safe Motherhood and Reproductive and Child Health (phase 1 and 2), have attempted to improve maternal health; however, they have not made the desired impact either because of an earlier emphasis on ineffective strategies, slow implementation as reflected in the poor use of available resources, or lack of effective ground-level governance, as exemplified by the widespread practice of informally charging users for free services. Thirty-two percent of women delivered in institutions in 2005-2006. A 2006 government scheme to give financial incentives for delivering in government institutions has led to substantial increase in the proportion of institutional deliveries. The availability of safe abortion services is limited, resulting in a large number of informal abortion service providers and unsafe abortions, especially in rural areas. The recent scheme of Janani Suraksha Yojana provides an opportunity to improve maternal and neonatal health, provided the quality issues can be adequately addressed. Key words: Delivery; Maternal health; Reproductive health; Skilled birth attendance; India doi: 10.3329/jhpn.v27i2.3369 J Health Popul Nutr 2009 April;27(2):271-292